Multi-method ADHD diagnostics in children: CBCL and TRF lead the way - Himmelmeier, Luisa; Waltereit, Robert; Werheid, Katja (Frontiers in Psychiatry, 2025)
ObjectiveDiagnosing ADHD in children requires multi-method examinations, yet the efficacy of this approach remains inconsistent. Our case control study investigated which standardized assessment methods most accurately predict an ICD-10 ADHD diagnosis in mixed settings (inpatient, outpatient, school).MethodsWe examined 125 children aged 6–13 years, thereof 56 with an ADHD diagnosis (M = 9.7, SD = 2.09) and 69 without (M = 9.04, SD = 2.05). Our assessment included a children’s self-report questionnaire (Youth Self Report 11-18R, YSR), which was exploratorily used for younger children, and two objective tests, a Gameboy-administered Go/No-Go-task (QIKtest, 1) and a PC-administered continuous performance test (CPT, 2). Parents were asked to complete some questions on the child’s possible diagnoses and medication, and a parent questionnaire (Child Behavior Checklist 6-18R, CBCL). Teachers received the same questionnaire in adapted form (Teacher’s Report Form 6-18R, TRF). Classification accuracy was determined using receiver operating characteristic (ROC) analyses (Sensitivity, Specificity, Area under the Curve and Diagnostic Odds Ratio). A stepwise combination of indices was used to explore a multi-method procedure and its diagnostic accuracy.ResultsCBCL and TRF achieved the highest classification accuracy focusing on inattention, followed by the YSR. Omission errors of CPT and QIKtest showed moderate classification performance while commission errors achieved the lowest. Combining CBCL, TRF and YSR showed superior diagnostic accuracy.ConclusionsOur results emphasize the relevance of multi-perspective questionnaire procedures for ADHD diagnosis despite potential acquisition challenges in clinical practice. Future research should develop more accurate objective test procedures and norm-based scales for children’s self-reports.